2015
DOI: 10.1111/apt.13354
|View full text |Cite
|
Sign up to set email alerts
|

Decreased fertility rates in 9639 women diagnosed with inflammatory bowel disease: a United Kingdom population‐based cohort study

Abstract: AimTo compare fertility rates in women with IBD to those in women without IBD and assess whether the relative fertility differed following IBD diagnosis, flares, and surgery. MethodsWomen aged 15 to 44 years in 1990-2010 were identified from a UK primary care database. We estimated overall and age-specific fertility rates by 5-year age bands for women with and without IBD.We used Poisson regression to calculate fertility rate ratios(AFRR), adjusted for age, smoking and socioeconomic deprivation. Results There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 27 publications
4
53
0
7
Order By: Relevance
“…A large population‐based study with 9639 women with IBD and 2 131 864 women without IBD, found women with CD experienced slightly lower birth rates (45.3 live births per 1000 person‐years), compared to those with UC (47.6 live birth per 1000 person‐years), or women from the general population (49.3 live births per 1000 person‐years). These rates were further impaired following active disease or surgery …”
Section: Introductionmentioning
confidence: 99%
“…A large population‐based study with 9639 women with IBD and 2 131 864 women without IBD, found women with CD experienced slightly lower birth rates (45.3 live births per 1000 person‐years), compared to those with UC (47.6 live birth per 1000 person‐years), or women from the general population (49.3 live births per 1000 person‐years). These rates were further impaired following active disease or surgery …”
Section: Introductionmentioning
confidence: 99%
“…The fertility maybe impaired as consequence of tubal adhesions, hydrosalpinx, dysfunction of fimbriae, or fallopian tube obstruction. The adjusted fertility rate ratio for colitis ulcerosa is 0.92 (95% CI 0.86-1.00) while it is 0.87 (95% CI 0.82-0.94) for Crohn's disease [6]. Lower fertility in CD may be attrib-uted to inflammation of the fallopian tubes and ovaries and dyspareunia in cases where the disease affects the perianal area [2].…”
Section: Influence On Fertilitymentioning
confidence: 97%
“…1,2 There is an increased risk of infertility with active Crohn disease (adjusted fertility rate ratio 0.70, 95% confidence interval 0.59-0.82). 3 A recent meta-analysis reported that patients with active disease before conception have a twofold increased risk of active disease during pregnancy. 4 A large registry cohort study involving 470 110 births confirmed that active Crohn disease during pregnancy is associated with an increased risk of stillbirth (adjusted odds ratio [OR] 4.48), preterm birth (adjusted OR 2.66) and low-birth weight infants (adjusted OR 3.30).…”
Section: What Should the Patient Be Told About Disease Activity And Pmentioning
confidence: 99%